2021
DOI: 10.3389/fcimb.2021.732001
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Antibiotic Resistance Characteristics of Vibrio Isolates From Rustic Environmental Freshwaters

Abstract: The study investigated the occurrence of antimicrobial resistance genes and virulence determinants in Vibrio species recovered from different freshwater sheds in rustic milieu. A total of 118 Vibrio isolates comprising Vibrio fluvialis (n=41), Vibrio mimicus (n=40) and V. vulnificus (n=37) was identified by amplification of ToxR, vmh and hsp60 genes. The amplification of virulence genes indicated that V. mimicus (toxR, zot, ctx, VPI, and ompU) genes were detected in 12.5%, 32.5%, 45%, 37.5% and 10% respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…Most resistant isolates harboured sul1 , sul2 and ermA resistant genes, encoded for the sulphonamide and erythromycin resistance. The study done by Gxalo et al (2021) reported that Vibrio spp. isolated from wastewater in aquatic sites were 100% resistant against polymyxin B and azithromycin, whilst more than 70% of the species were resistant to ampicillin, ampicillin‐sulbactam, cefuroxime and chloramphenicol.…”
Section: Wastewatermentioning
confidence: 99%
See 1 more Smart Citation
“…Most resistant isolates harboured sul1 , sul2 and ermA resistant genes, encoded for the sulphonamide and erythromycin resistance. The study done by Gxalo et al (2021) reported that Vibrio spp. isolated from wastewater in aquatic sites were 100% resistant against polymyxin B and azithromycin, whilst more than 70% of the species were resistant to ampicillin, ampicillin‐sulbactam, cefuroxime and chloramphenicol.…”
Section: Wastewatermentioning
confidence: 99%
“…isolated from wastewater in aquatic sites were 100% resistant against polymyxin B and azithromycin, whilst more than 70% of the species were resistant to ampicillin, ampicillin‐sulbactam, cefuroxime and chloramphenicol. Also, the antimicrobial resistance was confirmed by the presence of several ARGs, including beta‐lactam resistance genes ( bla TEM , AmpC , bla GES , bla IMP , bla OXA‐48 and bla KPC ), streptomycin resistance genes ( aadA and strA ), gentamicin resistance gene ( aphA1 ), quinolone resistance gene ( qnrVC ) and chloramphenicol resistance genes ( cmlA1 and catII ) (Gxalo et al, 2021). Also, Ho et al (2003) reported that all Vibrio spp.…”
Section: Wastewatermentioning
confidence: 99%
“…has been identified beyond the clinical territories. Antibiogram signatures revealed traits of resistance among Vibrio isolates from recreational beaches [ 60 ], coastal water [ 130 ], river water [ 131 ], and urban tropical estuary [ 20 ]. Additionally, surveillance results testified to the presence of carbapenem-resistant isolates in food such as salad [ 132 ] and seafood, particularly shrimps, mussels, and marine and freshwater fishes [ 27 , 28 , 29 , 30 , 31 , 34 , 75 , 81 , 83 , 121 , 133 , 134 ].…”
Section: Prevalence Of Carbapenem Resistancementioning
confidence: 99%
“…Reassuringly, a majority of the degrees of resistance are not high, mostly less than 10%, except for surveillance reports for environmental samples from Chhatak, Bangladesh [ 139 ], Lagos, Nigeria, Uganda [ 159 ], Eastern Cape, South Africa [ 131 ], Norway [ 83 ]; clinical samples in India [ 57 , 59 ]; seafood samples in Korea [ 134 ], Malaysia [ 27 , 32 ], Nigeria [ 121 ], and Egypt [ 75 ]. The antibiotic susceptibility pattern associated with the 16 Vibrio species covered in the existing surveillance report is highly diverse, with the carbapenem-resistance remarkably prevalent in V. parahaemolyticus [ 32 , 75 , 134 ], V. cholerae [ 59 , 140 ], V. vulnificus [ 60 ], V. fluvialis [ 57 , 131 ], V. anguillarum [ 83 ], and V. alginolyticus [ 75 ]. More worryingly, an increasing trend of intermediate-resistance transpires, indicating an evolution towards the expression of resistant phenotypes [ 140 ].…”
Section: Prevalence Of Carbapenem Resistancementioning
confidence: 99%
See 1 more Smart Citation